PROBLEMATIKA PENDIDIKAN TINGGI, KURIKULUM DAN PENDIDIK DI INDONESIA - Mukhamad Romdloni (Universitas Yudharta Pasuruan, 2021)
Education in Indonesia has experienced developments from time to time. Indonesia was once a beacon of education in Asia but is currently in decline. The educational comfort zone is formed when we are stuck in the routine of certification and accreditation without realizing the essence behind the importance of these activities. school today is intended only to obtain a diploma, not knowledge let alone skills. This is what will be explored in this article. educational reflection which is intended as a reminder for us that education is the task of the times and every era has the same educational task, namely glorifying and prospering human life. If our education today only raises workers and the mafia, it means that something is wrong in our education.